Simulation study of UWB interference effects on each WLANa frequency band - Abdullah A.; Ahmad A.; Sauti M.S.; Erana Y.; Shaaya S.A.; Mustafa I.S. (2023)
Currently, the advancement in Ultra-Wide Band (UWB) technology has caught the attention of many researchers to explore it given that its ability to support higher data rate with low transmission power. In spite of this, its capability to share the frequency spectrum with current narrowband and wideband radio services raises interference concerns for radio services. This study concerned with the effect of UWB interference on data rate performance in WLAN IEEE 802.11a system. 2008 IEEE.